2023
DOI: 10.3389/fimmu.2023.1307429
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of PE18, PE31, and PPE26 proteins from Mycobacterium tuberculosis in humans and mice

María García-Bengoa,
Emil Joseph Vergara,
Andy C. Tran
et al.

Abstract: IntroductionThe large family of PE and PPE proteins accounts for as much as 10% of the genome of Mycobacterium tuberculosis. In this study, we explored the immunogenicity of three proteins from this family, PE18, PE31, and PPE26, in humans and mice.MethodsThe investigation involved analyzing the immunoreactivity of the selected proteins using sera from TB patients, IGRA-positive household contacts, and IGRA-negative BCG vaccinated healthy donors from the TB endemic country Mozambique. Antigen-recall responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Although we did not test any vaccine candidate other than BCG in this study, we have shown previously that using this modified assay generates results that were correlated to lung bacterial load obtained in a mouse challenge study 37 . However, additional parallel experiments wherein the result of the modified assay are compared for multiple vaccine candidates and correlated with tissue bacterial burden in animal challenge experiments will further strengthen evidence as to whether the assay is more predictive of vaccine protection conferred in vivo than the conventional MGIA assay.…”
Section: Discussionmentioning
confidence: 95%
“…Although we did not test any vaccine candidate other than BCG in this study, we have shown previously that using this modified assay generates results that were correlated to lung bacterial load obtained in a mouse challenge study 37 . However, additional parallel experiments wherein the result of the modified assay are compared for multiple vaccine candidates and correlated with tissue bacterial burden in animal challenge experiments will further strengthen evidence as to whether the assay is more predictive of vaccine protection conferred in vivo than the conventional MGIA assay.…”
Section: Discussionmentioning
confidence: 95%